Integrated proteomics and phosphoproteomics revealed druggable kinases in neoadjuvant chemotherapy resistant tongue cancer - George, Irene A.; Sathe, Gajanan; Ghose, Vivek; Chougule, Anuradha; Chandrani, Pratik; Patil, Vijay; Noronha, Vanita; Venkataramanan, R.; Limaye, Sewanti; Pandey, Akhilesh; Prabhash, Kumar; Kumar, Prashant (Frontiers in Cell and Developmental Biology, 2022)
Tongue squamous cell carcinoma is an aggressive oral cancer with a high incidence of metastasis and poor prognosis. Patients with locally advanced technically unresectable tumors benefit from neoadjuvant chemotherapy as it reduces surgical resection, and controls distant metastasis, and locoregional recurrence. However, a significant number of patients develop resistance to the drug regimen. In this study, we identified the differential expression of proteins and altered phosphorylation events associated with neoadjuvant chemotherapy resistance. We integrated the proteomic and phosphoproteomic profiles of resistant (n=4) and sensitive cohorts (n=4) and demonstrated the differential expression and phosphorylation of proteins in the primary tissue of the respective subject groups. Furthermore, our study revealed a kinase signature associated with neoadjuvant chemotherapy resistance. Kinases such as MAPK1, AKT1, and MAPK3 are predicted to regulate the resistance in non-responders. Pathway analysis showed enrichment of Rho GTPase signaling and hyperphosphosphorylation of proteins involved in cell motility, invasion, and drug resistance. Targeting the kinases could help with the clinical management of neoadjuvant chemotherapy-resistant tongue cancer.